School leadership and management in South Africa: Findings from a systematic literature review. Issue 2 (14th March 2016) - Bush, Tony; Glover, Derek
Abstract : Purpose: – The purpose of this paper is to provide a systematic review of the literature on school leadership and management in South Africa, linked to the 20th anniversary of democratic government and integrated education. Design/methodology/approach: – The authors conducted a systematic review of all published work since 2007 with a more selective review of sources before 2007. Findings: – The findings show emerging evidence about the development of school leadership and management in South Africa but they also highlight on-going challenges, including poor learner outcomes, conflict with teacher unions, uneasy relationships between principals and school governing bodies, and leadership which remains focused on administration rather than teaching and learning. Research limitations/implications: – The findings show that research on school leadership and management is developing but remains limited in terms of its scope and a reliance on small-scale unfunded projects. Practical/implications: – The findings confirm the need for specialist leadership training for current and aspiring principals and for other senior and middle leaders. Social/implications: – The findings show that South Africa remains a divided society with great differences in the quality of education available to learners, based on social class rather than race. Originality/value: – The paper's value lies in the comprehensive and systematic review of research on school leadership.